Vienna Philharmonic concert in Budapest, conducted by Wilhelm Furtwängler, April 12, 1935 - Wiener Philharmoniker:::::::::::::::; Fürtwangler, Wilhelm, 1886-1954::::::::::::::: (Budapest; Hungary; F.K. Bdrczy, 2020)
Program for an all-Beethoven concert by the Vienna Philharmonic, conducted by Wilhelm Furtwängler, in Budapest, Hungary, on April 12, 1935. The program included the Egmont Overture, op. 84, the Pastoral Symphony, op. 68, and the Fifth Symphony, op. 67.